Meta-analiza korelacije između visokog izraza LNCRNA NEAT1 u rektalnom raku i patološkim karakteristikama i prognozama: NEAT1 lncRNA in Rectal Cancer: Prognosis - Xu, Guoxi; Lin, Qiyi; Pan, Jianpeng; Wang, Huaishuai; Li, Yinlin; Zhuang, Yixiang; Chen, Jianpeng; Lin, Gaofeng; Liu, Weibo (Journal of Medical Biochemistry, 2024)
Background: To systematically evaluate the relationship between the expression level of long noncoding RNA NEAT1 and the clinical characteristics and prognostic value of rectal cancer patients.Methods: PubMed, EMBASE, Cochrane library database and case-control studies on the correlation between abnormal expression of lncRNA NEAT1 and prognosis of rectal cancer patients published by the American clinical trials registry before May 1, 2023 were searched. The search time was from the establishment of the database to May 30, 2023.Results: A total of 7 case-control studies were included, including 1063 cancer patients. The results of meta-analysis showed that the high expression of lncRNA NEAT1 was significantly correlated with the degree of differentiation [or=0.45, 95%CI=0.32-0.63, P